2012
DOI: 10.2196/jmir.1818
|View full text |Cite
|
Sign up to set email alerts
|

Speech Perception Benefits of Internet Versus Conventional Telephony for Hearing-Impaired Individuals

Abstract: BackgroundTelephone communication is a challenge for many hearing-impaired individuals. One important technical reason for this difficulty is the restricted frequency range (0.3–3.4 kHz) of conventional landline telephones. Internet telephony (voice over Internet protocol [VoIP]) is transmitted with a larger frequency range (0.1–8 kHz) and therefore includes more frequencies relevant to speech perception. According to a recently published, laboratory-based study, the theoretical advantage of ideal VoIP conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…These findings are in line with speech perception test results performed under simulated laboratory conditions [20]. …”
Section: Discussionsupporting
confidence: 90%
“…These findings are in line with speech perception test results performed under simulated laboratory conditions [20]. …”
Section: Discussionsupporting
confidence: 90%
“…Lidestam and colleagues found in a preliminary study that the addition of video can potentially aid understanding, but pointed out audio-video synchrony as an area of concern [12]. Mantokoudis and colleagues investigated the potential benefits of Internet telephony for people with hearing loss, but concluded that more research was needed to determine the impact of less than ideal conditions [13].…”
Section: Related Workmentioning
confidence: 99%
“…However, clients were interested in tele-audiology to reduce waiting times and costs, but a common barrier for using it was that they preferred face-to-face appointments ( Eikelboom and Atlas, 2005 ). Also, hearing aid users with severe forms of hearing loss cannot easily use the telephone but can do better if using video chat programs instead of the telephone ( Mantokoudis et al, 2012 ). The client attitudes towards and interest in tele-audiology applications suggest that a combination of tele-audiology and face-to-face appointments may increase client satisfaction with the audiologic rehabilitation.…”
Section: Introductionmentioning
confidence: 99%